Biological nitrogen fixation in cereals: An overview - Sharma, Pooja; Devi, Geeta; Sharma, Manisha; Mamrutha, Harohalli Masthigowda; Venkatesh, Karnam; Tiwari, Vinod; Singh, Gyanendra Pratap; Sharma, Pradeep (Journal of Cereal Research, 2016)
Cereals like rice, wheat, maize, sorghum and millets are the cropswith total annual yields of 2000 million tons whereas two-thirdpopulation consumes only wheat worldwide. Demand for cereals isgradually increasing so there is a need to improve the agronomicand molecular parameters to enhance the quality and productivity ofcereals. Nitrogen is one of the essential nutrients required by plants;however, cereals are unable to directly uptake nitrogen from theenvironment. The nitrogen content of soil is maintained either thoughfertilizer or organic farming. An excess use of nitrogen compoundsin any form like water, air, and soil wreaks havoc on the delicaterhizosphere. An alternative sustainable solution is the incorporationof biological nitrogen fixation into cereals that reduces the undesiredeffects of chemical nitrogen. In this review article we will discussinghow the fertility of soil is maintained using diazotrophs and geneticallyengineering in nitrogen fixing pathways in cereals.